The Digitalization Technology for Sustainable Rural Entrepreneurship: A Structured Review - Norsamsinar Samsudin, Cik Thuraiya Zakaria, Juliana Haji Osman @ Zainal Abidin, Mohamad Rohieszan Ramdan, Intan Khasumarlina Mohd Khalid, Hafizul Fahri Hanafi (Tanjung Malim, 2024)
The Digitalization Technology for Sustainable Rural Entrepreneurship: A Structured Review by Norsamsinar Samsudin, Cik Thuraiya Zakaria, Juliana Haji Osman @ Zainal Abidin, Mohamad Rohieszan Ramdan, Intan Khasumarlina Mohd Khalid, Hafizul Fahri Hanafi